Effectiveness of active occupational therapy in patients with acute stroke: A propensity score-weighted retrospective study - Yamakawa, Shiori; Nagayama, Hirofumi; Tomori, Kounosuke; Ikeda, Kohei; Niimi, Ayaka (Frontiers in Rehabilitation Sciences, 2023)
Background and Purpose The effects of therapy and patient characteristics on rehabilitation outcomes in patients with acute stroke are unclear. We investigated the effects of intensive occupational therapy (OT) on patients with acute stroke. Methods We performed a retrospective cohort study using the 2005–2016 Japan Rehabilitation Database, from which we identified patients with stroke (n = 10,270) who were admitted to acute care hospitals (n = 37). We defined active OT (AOT) and non-AOT as OT intervention times (total intervention time/length of hospital stay) longer or shorter than the daily physical therapy intervention time, respectively. The outcomes assessed were the Functional Independence Measure (FIM) and National Institutes of Health Stroke Scale (NIHSS) scores, duration of hospitalization, and rate of discharge. Propensity scores and inverse probability of treatment weighting analyses adjusted for patient characteristics were performed to investigate the effects of AOT on patient outcomes. Results We enrolled 3,501 patients (1,938 and 1,563 patients in the AOT and non-AOT groups, respectively) in the study. After inverse probability of treatment weighting, the AOT group had a shorter length of hospitalization (95% confidence interval: −3.7, −1.3, p < 0.001), and the FIM (95% confidence interval: 2.0, 5.7, p < 0.001) and NIHSS (95% confidence interval; 0.3, 1.1, p < 0.001) scores significantly improved. Subgroup analysis showed that lower NHISS scores for aphasia, gaze, and neglect and lower overall NIHSS and FIM scores on admission led to a greater increase in FIM scores in the AOT group. Conclusions AOT improved the limitations in performing activities of daily living (ADL) and physical function in patients with acute stroke and reduced the length of hospitalization. Additionally, subgroup analysis suggested that the increase in FIM score was greater in patients with severe limitations in performing ADLs and worse cognitive impairment, such as neglect, on admission.